Development of A Drama Learning Guide For Class XI High School Students - Yuwita, Yessi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2024)
This research aims to develop a drama learning guide that suits the needs of class XI high school students. The research method used is the research and development (R&D) method following the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The analysis stage was carried out to identify student needs and characteristics of drama learning in high school. Next, a drama learning guide was designed according to the analysis findings, and drama learning materials were developed taking into account the principles of effective teaching. Implementation of the guide was carried out in class XI Senior High School, and an evaluation was carried out to evaluate the effectiveness of the drama learning guide. It is hoped that the results of this research can contribute to improving the quality of drama learning in high school and provide useful guidelines for teachers in designing interesting and effective drama lessons.